Emigrazione economica dei giovani polacchi come fattore significativo di sfide all’interno del matrimonio e della famiglia nella perspettiva canonistica - Aleksandra Brzemia-Bonarek (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II, 2018)
In Poland, in the last 25 years, theologians, lawyers, sociologist and psychologists have discussed significant changes in the field of marriage and family. The political transfor - mations caused not only economic development, but also cultural transformation and globalization of social phenomena. Among such issues there is the problem of the emi- gration of young polish citizens. Apart from the positive economic and cultural aspects of working abroad, some negative influence on the strength and unity of the families has been observed. In the article effort was made to examine the impact of labor migration on the reorientation of the general family in the light of matrimonial nullity processes, where the emigrant was involved as the Petitioner or the Respondent party. The author`s conclusion is that it is the last chance to create and put into practice, as soon as possible, the modern and interdisciplinary program of pastoral care directed to the families of the migrants, especially the new generation.